Effect of curcumin dose, treatment duration and intervention type on tumor inhibition in animal models: a systematic literature review using meta-analysis techniques - Nasruddin, Arina; Amid, Azura (IIUM Press, 2019)
Curcuma longa L. uses widely as a traditional medicine especially in India and China for the treatment of diabetic wounds, inflammatory, hepatic, and digestive disorders. These effects lead to the research of this plant for the treatment of chronic diseases. To assess the tumour inhibition effect of curcumin in animal models by integrating various studies into a systematic literature review (SLR) and meta-analysis. Studies of curcumin treatment in tumor-induced animal models were searched in electronic databases. The assessment of the quality of the studies included and the tumor inhibition effect used SYRCLE’s Risk of Bias tool and Review Manager (The Cochrane Collaboration) software. From the 732 articles identified, only 11 studies met the selection criteria and included in the analysis. Curcumin significantly inhibited the tumor volume in the animal models in overall, and the subgroup analyses revealed that high dose, long-duration curcumin treatment, and intervention by injection have a more significant effect compared to the opposite group. Curcumin was effective in inhibiting tumor volume in animal models. The study quality and heterogeneity of the meta-analysis can probably be improved if a larger-scale bases of animal models and a well-designed study were available.